Efficacy of diode and CO2 lasers along with calcium and fluoride-containing compounds for the remineralization of primary teeth - Elham Soltanimehr; Ehsan Bahrampour; Zeynab Yousefvand (BMC, 2019)
Abstract Background This study aimed to assess the efficacy of a 980-nm diode and 10.6-μm CO2 laser accompanied by tricalcium phosphate-5% sodium fluoride (fTCP) and casein phosphopeptide amorphous calcium phosphate (CPP-ACP) for the remineralization of primary teeth. Methods In total, 117 extracted primary anterior teeth were randomly divided into eight experimental and one control group: (I) control (polished enamel), (II) fTCP varnish, (III) fTCP + diode laser, (IV) fTCP + CO2 laser, (V) CPP-ACP, (VI) CPP-ACP + diode laser, (VII) CPP-ACP + CO2 laser, (VIII) diode laser, and (IX) CO2 laser. The microhardness of 12 samples in each group and the enamel porosity of one sample in each group were assessed before and after demineralization and 28 days after remineralization. Data were analysed using two-way ANOVA. Results Significant differences existed in microhardness (P = 0.004) and percentage of remineralization (P < 0.001) after remineralization among the material groups such that the highest mean was noted in the CPP-ACP group. No significant difference was noted in microhardness (P = 0.052) or percentage of remineralization (P = 0.981) after remineralization among the laser groups. In all groups, porosities increased after demineralization and slightly decreased after remineralization; the greatest reduction in porosity of the material groups was noted in the fTCP group, and the CO2 group among the laser groups. The interaction effect of materials and lasers was not significant (P > 0.05). Conclusion The highest microhardness was achieved after remineralization with CPP-ACP. The efficacy of the diode and CO2 lasers was the same. No synergistic effect was found between materials and lasers. Trial registration This is not a human subject research.